Comparision of open slot angle for asymmetry slot antenna using 3D finite element method - Thaiwat, K.; Nantivatana, P.; Phasukkit, P.; Tungjitkusolmun, S.; Sangworasil, M. (My University, 2011)
This paper presents analysis of asymmetry slot antenna configuration for microwave ablation at 2450 MHz using three-dimensional finite element analyses treatment for liver tissue. We designed new coaxial-slot antenna is opened slot at one-side of antenna. We study heat transfer for liver tissue by used MW Ablation system, varying the angle of open slot at 90°, 180°, 270° and 360°. The results illustrate that the coaxial-slot asymmetry structure antenna can be used in microwave ablation for treatment of the liver cancer tissue. Areas of treatment depend on angle of open slot, power and operated time which we can control destruction of the cancer cell in the area closed to the very fragile tissue or blood vessel. © 2011 IEEE.
Keywords: Finite Element; liver cancer; Microwave Ablation